Tumasik: Sejarah Awal Islam di Singapura (1200-1511 M) - Asep Saefullah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
This article attempts to trace the early history of Islam in Temasek, a former name of Singapore. The city was also known as the ‘Sea Town’, and was a part of the Nusantara. In the 12th-14th century, Tumasik and Kedah were important ports in the Malay Peninsula. Tumasik, at that time, was important enough to figure in international trade networks. The very strategic location of Tumasik, at the very tip of the Malay Peninsula, made it a significant prize for the master. Kingdoms that once ruled it: the Sriwijaya kingdom until the end of the 13th century AD and Majapahit kingdom that ruled it until the 14th century. In the 15th century AD, Tumasik came under the rule of Ayutthaya-Thailand; and subsequent occupation controlled by the Sultanate of Malacca to the Portuguese in 1511 AD. Speaking on the comming of Islam in Tumasik that was along with the influx of Muslim merchants, both Arabic and Persian, between the 8th – 11th century which the trading activity increased in the Archipelago. Coastal cities and ports, one of which Tumasik, on the Malay Peninsula became the settlements of Muslim tradespeople. Most of them settled and married there. Thus, it is strongly suspected that Islam has been present in Tumasik since perhaps the 8th century AD. Up until the beginning of the 16th century, the old Singapore remains a Muslim settlement, along with other vendors, both from Europe, India, and China, and also became an important port under the Sultanate of Malacca. That Malaccan empire was conquered by the Portuguese in 1511. Keywords: early history of Islam, Tumasik, Singapore, Sultanate of Malacca Artikel ini mencoba menelusuri sejarah awal Islam di Tumasik, kada disebut juga Temasek, nama dulu bagi Singapura. Kota ini juga disebut sebagai Kota Laut (Sea Town), dan merupakan bagian dari Nusantara masa lalu. Pada abad ke-12 s.d. 14 M, Tumasik bersama Kedah merupakan pelabuhan-pelabuhan penting di Semenanjung Malaya. Pada masa itu, Tumasik merupakan kota perdagangan yang cukup besar dan penting dalam jaringan perdagangan internasional. Posisinya yang sangat strategis di ujung Semenanjung Malaya, menjadikan Tumasik menggiurkan untuk dikuasai. Kerajaan-kerajaan yang pernah menguasai Tumasik yaitu Sriwijaya sampai akhir abad ke-13 M dan Majapahit sampai abad ke-14 M. Pada abad ke-15 M, Tumasik berada di bawah kekuasaan Ayutthaya-Thailand; dan selanjutnya dikuasai Kesultanan Malaka sampai pendu¬dukan Portugis 1511 M. Adapun proses masuknya Islam di Tumasik terjadi bersamaan dengan masuknya para pedagang Muslim, baik dari Arab maupun Persia pada abad ke-8 s.d. 11 M yang mengalami peningkatan aktivitas perdagangan. Kota-kota pesisir dan pelabuhan-pelabuhan, salah satunya Tumasik, di Semenanjung Malaya menjadi pemukiman-pemukiman bagi para pedagang Muslim tersebut. Sebagian dari mereka menetap dan berkeluarga di sana. Dengan demikian, diduga kuat bahwa Islam telah hadir di Tumasik antara abad ke-8 M - ke 11 M. Hingga permulaan abad ke-16 M, Singapura lama tetap menjadi pemukiman Muslim, bersama para pedagang lain, baik dari Eropa, India, maupun Cina, dan sekaligus menjadi pelabuhan penting di bawah kekuasaan Kesultanan Malaka, sampai dengan kesultanan ini ditaklukan oleh Portugis pada 1511 M. Kata kunci: sejarah awal Islam, Tumasik, Singapura, Kesultanan Malaka